Materials requirements planning through an application based on particle swarm optimization (2017)
This work approaches the Material Requirements Planning (MRP) problem through a Particle Swarm Optimization (PSO) based algorithm. Results from various computer experiments are carried out considering different production capacity levels, where the algorithm shown good performance. It can be observed that the solutions found by the algorithm surpass by 6.31% the solution presented in the reviewed literature. © 2017.